Pengaruh Brand Image, Diskon Dan Kualitas Produk Terhadap Keputusan Pembelian Tas Melalui Harga Pada Aplikasi Online Shop (Tiktok Shop) - Anggun Mardiyah; Yulasmi; Deni Saputra (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This research aims to test how much influence brand image, discounts and product quality have on bag purchasing decisions via price in the online shop application (Tiktok Shop). This research is quantitative research. The data collection method is through distributing questionnaires. This sampling technique uses a non-probability sampling technique with a convenience sampling technique using the Slovin formula. The analytical methods used are path analysis, partial least squares (PLS) analysis, outer model, inner model and hypothesis testing, data processing in research using the SmartPLS 3.0 software program. The results of the research can be concluded that there is a positive and significant influence between Brand Image and Price among students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and significant influence between discounts on prices for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use the Tiktok Shop. There is a positive and significant influence between work discipline on prices for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and significant influence between Brand Image on purchasing decisions for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and significant influence between discounts on purchasing decisions for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and insignificant influence between product quality on purchasing decisions for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and insignificant influence between price on purchasing decisions for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and insignificant influence between brand image on purchasing decisions through price as an intervening variable for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and insignificant influence between discounts on purchasing decisions through price as an intervening variable for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop. There is a positive and insignificant influence between product quality on purchasing decisions through price as an intervening variable for students majoring in management at Putra Indonesia University "YPTK" Padang Bp 2021 who use Tiktok Shop.